More Rational or More Emotional Than Others? Lay Beliefs About Decision‐Making Strategies - VanBergen, Noah; Lurie, Nicholas H.; Chen, Zoey (Journal of Consumer Psychology, 2022)
Research demonstrates that people utilize both reasoning and feeling in decision making and that both strategies can be advantageous. However, little is known about how people perceive their decision‐making relative to others. Despite research findings and popular appeals supporting the use of affective decision processes, across a series of studies, we find that individuals believe they rely more on reasoning, and less on feelings, than others. These effects are driven by the motivation to self‐enhance where, in most contexts, individuals believe the use of reasoning is superior, and self‐enhancing, compared to the use of feelings. Consistent with this mechanism, beliefs that one’s decisions are more rational than others’ are as follows: (a) stronger for those who exhibit greater beliefs in the superiority of reasoning (vs. feeling), (b) attenuated when the decision context precludes motivational thinking about the self or the self is affirmed, and (c) reversed when the use of feelings is perceived as more self‐enhancing. We demonstrate downstream consequences (e.g., decision delegation), rule out alternative explanations, and discuss practical implications of these lay beliefs.